2008
DOI: 10.22179/revmacn.10.275
|View full text |Cite
|
Sign up to set email alerts
|

Causes and contrasts in current and past distribution of the white shark (Lamniformes: Carcharodon carcharias) off southeastern South America

Abstract: Abstract:The great white shark is a cosmopolitan temperate marine species which is rare in Argentina, Uruguay, and Brazil today. Several publications include the white shark as inhabiting Patagonian waters. However, there is no recent or fossil record of the white shark south of S 38° 30´ in the southwestern Atlantic. A tooth found in Quaternary sediments at Pehuencó (S 38° 56´), southern Buenos Aires province, is the southernmost occurrence of the species in the southwestern Atlantic. The occurrence of C. car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This study allowed for the retrieval and addition of two more records of the presence of the white shark Carcharodon carcharias in Brazilian waters (Figure 4), previously reported as rarely occurring on the Atlantic coast of South America (Gadig and Rosa 1996;Cione and Barla 2008;Amorim et al 2018), but confirmed by the fisher survey concerning records, containing both information and photographic evidence. The oldest account, concerning the capture of a C. carcharias in 1968, was reported by a 76-year-old fisher who reported a size of 11 m and 6 ton.…”
Section: Ethno-names and Historical Recordsmentioning
confidence: 59%
See 1 more Smart Citation
“…This study allowed for the retrieval and addition of two more records of the presence of the white shark Carcharodon carcharias in Brazilian waters (Figure 4), previously reported as rarely occurring on the Atlantic coast of South America (Gadig and Rosa 1996;Cione and Barla 2008;Amorim et al 2018), but confirmed by the fisher survey concerning records, containing both information and photographic evidence. The oldest account, concerning the capture of a C. carcharias in 1968, was reported by a 76-year-old fisher who reported a size of 11 m and 6 ton.…”
Section: Ethno-names and Historical Recordsmentioning
confidence: 59%
“…The white shark C. carcharias is an emblematic species in the popular imagination, rare in Brazilian waters and with only a few dozen occurrences recorded along the coast, with Rio de Janeiro being the northernmost area of South American occurrences (Gadig and Rosa 1996;Cione and Barla 2008). The oldest record reported by fishers was from 1968, with the specimen being called an anequim-boto, followed by another more recent incident, in 2010.…”
Section: Ethno-names and Historical Recordsmentioning
confidence: 99%
“…These specimens are found mixed on the same beaches with other marine vertebrates coming from more recent Holocene beds (e.g. Cione, 1983;Cione & Barla, 2008). However, the age of the specimens described here is uncertain because the geology of the marine platform is rather complex and includes a succession of diverse stratigraphic units.…”
Section: Geological Settingsmentioning
confidence: 75%
“…Possibly some of the above-mentioned stratigraphical units, such as DS5 or DS4, may be correlated to the sandy beds informally known as the "Puelchense" (see Parker et al, 2008). The "Puelchense" beds are partially correlated with Miocene-Pliocene beds close to Paraná city based on its fossil record (see discussion in Cione & Barla, 2008) and belong to a subterranean aquifer that extends along a large portion of the subsoil of Buenos Aires Province, up to the Mar de Ajó locality (see also Auge et al, 2002). The "Puelchense" beds yielded several fossils studied by Carlos Rusconi in the 1930s during the extraction of sand destined for construction (Rusconi, 1933;1934;Cione & Barla, 1999;Chimento, 2012).…”
Section: Geological Settingsmentioning
confidence: 99%
“…New molecular tools such as environmental DNA (eDNA) sequencing, which uses filtered water samples to noninvasively identify species from trace DNA, can contribute toward understanding movement patterns of large migratory marine fauna such as sharks and cetaceans at species and community level (Larson et al, 2017;Bakker et al, 2017;Baker et al, 2018), and pinpointing habitat use by endangered sawfishes (Simpfendorfer et al, 2016). For instance, although white sharks appear to be exceptionally rare in South American waters, archeological and historical evidence suggest resident populations may have been extirpated by intense fishing (Cione and Barla, 2008;Amorim et al, 2017). Fisher interviews, aerial surveys, and eDNA surveys around pinniped colonies could be used to determine if white sharks persist in areas in South America where they were previously documented as well as other areas.…”
Section: Where and How Frequent Are White Sharks Outside Their Key Knmentioning
confidence: 99%